(untitled) (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2016)
The customer service quality depends on the procedure of the application maintenance in data center of the communication provider. In the article the control approach of dynamic resource involvement has been suggested in order to ensure the input flow maintenance that takes into account the random nature of applications’ inflow and utilizes both short-term and long-term load statistics. The proposed approach consists of two methods that manage the number of the implicated serving nodes. The first one verifies the resource amount adequacy, provides the evaluation of input load’s dynamics based on the short-term statistics as well as the current state of the technical facilities. The second one accounts for the long-term statistics according to which the implication of additional resources can be scheduled during the load peaks. The simulation results of technical resources management have been presented for the data center infrastructure of the communication provider, that prove the effectiveness of the proposed methods.